2009
DOI: 10.1007/s00405-009-1171-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteoplastic atticoantrotomy with autologous bone chips and a bony attic strut in cholesteatoma surgery

Abstract: The objectives of this study were to determine whether autologous bone chips are suitable materials for canal wall reconstruction after cholesteatoma removal and to evaluate the effectiveness of a separate attic bone graft for the prevention or recurrent cholesteatomas using prospective study of two consecutive patient series (29/31 unselected patients with an average follow-up of 36.3 +/- 11.1/21.5 +/- 6.3 months) and retrograde resection of the posterior-superior canal wall followed by reconstruction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The collumela was placed directly on the stapes footplate. This is similar to the conclusion of the studies that observed the results of atticotomy to hearing and recurrence rate by Kim et al (1) and Gerhrking (2).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The collumela was placed directly on the stapes footplate. This is similar to the conclusion of the studies that observed the results of atticotomy to hearing and recurrence rate by Kim et al (1) and Gerhrking (2).…”
Section: Discussionsupporting
confidence: 92%
“…If the cholesteatoma is limited to the tympanic cavity this procedure prevents for opening the mastoid air cells. Many authors favor canal wall up tympanoplasty (CWUp) with attic reconstruction over canal wall down tympanoplasty (CWD) (2,5). Although the intraoperative visualization of the posterior tympanic space and mastoid in CWUp tympanoplasty is limited and cholesteatoma recurrence rate is higher, it provides close to anatomic shape of the postoperative tympanic cavity, proper basis for ossicular reconstruction and consequently better hearing then CWD tympanoplasty (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction has been performed using a variety of materials, with various results (3Y9). It has been shown that use of a patient's own bone, such as reimplantation of the previously removed posterior canal wall or the use of cortical bone, often results in necrosis (10,11). Foreign materials, even those known to be biocompatible, always bear a risk of nonacceptance in the special environment of the middle ear and mastoid.…”
Section: Discussionmentioning
confidence: 99%
“…Going back to studies following different techniques, Gehrking E [10] stated that osteoplastic atticoantrotomy with autologous bone chip reconstruction enables a tailor made anatomical and physiological reconstitution of auditory ear canal thus enhancing the acoustic properties. Precise reconstruction of lateral attic wall and reinforcement of superior part of tympanic membrane seemed important for prevention of recurrent cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%